Effects of physical prehabilitation on markers of endothelial function in patients undergoing elective coronary artery bypass grafting. (14th October 2021) - Argunova, Y; Belik, E; Gruzdeva, O; Barbarash, O
Abstract: Purpose: To evaluate the effects of preoperative exercise training on the perioperative serum levels of asymmetric dimethylarginine (ADMA) and endothelin-1 (ET-1) in patients with stable coronary artery disease (CAD). Methods: 78 male patients with stable coronary artery disease referred to elective on-pump CABG were screened and randomized either to receive prehabilitation, or routine preoperative management without training. Group 1 (n=43, age 61.5 [55; 65] years) patients underwent preoperative exercise training (treadmill sessions at 80% of peak oxygen uptake (VO2peak) intensity for 5–10 days), whereas group 2 (n=35, age 63.0 [56; 66] years) received routine preoperative management without training. Levels of endothelial function (ADMA and ET-1) were measured using enzyme immunoassay in the preoperative period of CABG before exercise training, the day before surgery, and in the postoperative period on days 5–7. Logistic regression analysis was used to determine significant risk factors contributing to postoperative complications in the early postoperative period. Statistical analysis was performed using the Statistica 10.0 software (Statsoft, USA). Results: Patients from both study groups did not differ in the main preoperative clinical and demographic parameters. They had similar comorbid profile and were also comparable in terms of the intraoperative parameters. No differences in baseline echocardiography and cardiopulmonary exercise testing were reported. By the end of the exercise training, group 1 patients had a significantly lower level of ADMA than patients from group 2 without prehabilitation (p=0.01). Correlation analysis reported a direct correlation between the levels of ADMA and ET-1 the day before surgery (ρ = 0.28, P=0.04) in the absence of significant intergroup differences in ET-1 levels. Stepwise logistic regression adjusted for comorbidities (chronic bronchopulmonary disease) and intraoperative risk factors (aortic cross-clamp time) reported a correlation of the pre-existing diabetes with an increased risk of complications in the early postoperative period (OR 12.3, 95% CI [1, 18–127.6], p=0.03). Elevated ET-1 levels also increased the risk of complications (OR 10.7, 95% CI [1.1–105.2], p=0.03), whereas preoperative exercise training reduced the risk of postoperative complications (OR 0.1, 95% CI [0.01–0.82], p=0.02). Conclusion: Our findings indicate favorable effects of prehabilitation on the improvement of endothelial function and prevention of the complications in the early postoperative period. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Fundamental topic No. 0546-2019-0003